Psychological distress among Brazilian workers during the initial stage of the COVID-19 pandemic: a descriptive study - Alonso, Melissa Spröesser; Lima, Maria Cristina Pereira; Dias, Adriano; Camacho-Vega, Juan Carlos; García-Iglesias, Juan Jesus; Ruiz-Frutos, Carlos; Bernardes, João Marcos; Gómez-Salgado, Juan (Frontiers in Public Health, 2024)
Background COVID-19 pandemic imposed drastic and abrupt changes to working environment and organization and that might have caused additional negative effects on mental health. Thus, this study aimed to quantify and assess the severity of psychological distress experienced by Brazilian essential and nonessential workers during the first months of the COVID-19 pandemic. Methods This descriptive study included 2,903 participants who answered an online questionnaire between April and May 2020. The research questionnaire was translated and culturally adapted to the Brazilian population from a questionnaire developed and validated for the Spanish population. Variables were analyzed using simple and cumulative percentage distributions and measures of central tendency and dispersion. The Wilson score interval was used to calculate confidence interval (CI) for the main outcome, psychological distress. Results It was observed a high prevalence (72.6%) of psychological distress among the study’s participants. They also presented a median risk perception score of 60 (out of a maximum of 90), and their greatest concern was transmitting the virus to family members, close contacts or patients. Furthermore, it was found a lower sense of coherence and work engagement among the participants than those observed in previous studies conducted in other countries. Conclusion Almost three quarters of the study’s participants were classified as presenting psychological distress. Thus, it is imperative to provide mental health remotely delivered interventions to workers during public health events that require prolonged social distancing measures.